Strategi Guru PAI dalam Membentuk Akhlak Peserta Didik di Era Digital pada SMK NU Darussalam Rejoagung Srono - Mas Hilmi Mubarrok; Saiful Gufron Duwila; Safta Hidayat; Slamet Slamet (Jurnal Wahana Literasi Pendidikan, 2026)
The rapid development of information and communication technology has brought significant changes to learning patterns, social interactions, and the moral development of students, particularly in Vocational High Schools (SMK), where adolescents are highly vulnerable to the influence of digital culture. This study aims to conduct an in-depth analysis of the strategies employed by Islamic Education (PAI) teachers in shaping students’ character at SMK NU Darussalam Rejoagung Srono, as well as to examine the challenges that arise amid the rapid flow of digitalization, which presents both opportunities and obstacles. Using a qualitative research method with a descriptive case study approach, this research describes the phenomenon naturally based on the experiences of teachers and students as primary subjects. The findings indicate that character-building strategies are implemented through exemplary behavior (uswah hasanah), the integration of moral values in learning activities, the positive utilization of digital media, routine worship practices, and individualized spiritual guidance that helps students understand Islamic values in a contextual and digitally relevant manner. However, PAI teachers face various challenges such as limited digital literacy, inadequate technological facilities, weak parental supervision, and the strong penetration of negative digital content that often contradicts Islamic moral values. This study concludes that the effectiveness of character formation greatly depends on the consistency of teacher strategies, institutional support, and synergy between school and family so that character education can adapt to digital-era developments and foster a generation that is virtuous, religious, and wise in utilizing technology.